A Suitable Distance? Revisiting a Millennial Approach to Curating Art in the Caribbean. Issue 3 (3rd July 2022) - Wainwright, Leon
Abstract: In the autumn of 2006, Soft Box Studios, a small, privately run art gallery in Port of Spain, Trinidad, staged the exhibition A Suitable Distance, comprising twenty-one paintings by artists who were at that time living on the island yet who hailed from elsewhere. Curated by Andy Jacob, a teacher and former deputy curator of Trinidad and Tobago's National Museum and Art Gallery, the five featured artists were Kofi Kayiga (b. 1943) and Roberta Stoddart (b. 1963)—who have a Jamaican background—alongside Chris Ofili (b. 1968), Rex Dixon (b. 1939), and Peter Doig (b. 1959), who are originally from the United Kingdom. Revisiting the approach taken to curating this group of foreign artists involves looking at the conditions of production and reception for this art and, more generally, for art in the Caribbean, during the first decade of the millennium. Reflecting on this period from a present-day perspective allows A Suitable Distance to be historicized as a millennial approach to curatorial projects that engage with both the global art world and the Caribbean's local art world, and allows us to assess the geographical and metaphorical distances between them as well as their intersections. The conclusions encourage the continued foregrounding of critical frameworks of analysis and the problematizing of the terms of visibility and success that surround contemporary art and art communities of the Caribbean.